Early cirrhosis and a preserved bone marrow niche favour regenerative response to growth factors in decompensated cirrhosis. (10th August 2018) - Anand, Lovkesh; Bihari, Chhagan; Kedarisetty, Chandan K.; Rooge, Sheetalnath B.; Kumar, Dhananjay; Shubham, Smriti; Kumar, Guresh; Sahney, Amrish; Sharma, Manoj K.; Maiwall, Rakhi; Kumar, Anupam; Sarin, Shiv K.
Abstract: Background: Exogenous growth factor‐mobilized bone marrow (BM) stem cells have shown a differential response in the management of decompensated cirrhosis (DC). This study was designed to evaluate potential clinical benefit of adding Erythropoietin (EPO) in granulocyte‐colony stimulating factor (G‐CSF)‐mobilized stem cell therapy, possible mechanisms of regeneration and predictive factors of regenerative response. Methods: Sixty consecutive DC patients received either G‐CSF with EPO (Group A; n = 30) or G‐CSF and placebo (Group B; n = 30) for 2 months and were carefully followed up for 1 year. Baseline and post‐treatment liver biopsy, BM biopsy and BM aspirate were analysed for fibro‐inflammatory and regenerative response and BM hematopoietic reservoir. Results: Addition of EPO to G‐CSF showed a significant improvement in Child‐Pugh score ( P  = 0.03) and MELD score ( P  = 0.003) as compared to G‐CSF alone, with reduction in mortality (16.6% vs 36.7%, P  = 0.09). The combination arm also demonstrated a decreased incidence of acute kidney injury ( P  < 0.001), encephalopathy ( P  = 0.005) and refilling of ascites ( P  = 0.03). Compared to monotherapy, it increased CD163+ macrophages ( P  = 0.013), Ki67+ index ( P  < 0.001) with decrease in α‐SMA levels ( P  < 0.001) in liver tissue. The response was better with grade 1 and 2 than with grade 3 ascites; Child B cirrhosis and MELD < 16. Non‐responders had lower hematopoietic stem cells (HSCs) at baseline. On multivariate analysis, the liver disease severity (MELD < 16) and a relatively preserved BM (BM‐HSCs > 0.4) predicted therapeutic response (AUROC = 0.82). Conclusions: Early DC (MELD < 16) patients with mild‐moderate ascites and those with a healthy cellular baseline BM respond better to growth factor therapy. Addition of EPO to G‐CSF provides better regenerative response than G‐CSF monotherapy.